Impact of Oxytocin Massage on Lactation in Postpartum Mothers: A Quasi-Experimental Study at Puskesmas Sungai Paduan - Asnawati; Rifzul Maulina (CV. Publikasi Indonesia, 2026)
The postpartum period is a critical stage in maternal recovery and adaptation, during which successful breastfeeding plays an essential role in ensuring optimal infant growth and maternal health. However, inadequate breast milk production during the early postpartum period remains a major challenge that contributes to the low rate of exclusive breastfeeding. Oxytocin massage has been introduced as a simple, safe, and non-pharmacological intervention to stimulate oxytocin secretion and improve the milk ejection reflex. This study aimed to determine the effect of oxytocin massage on breast milk production among postpartum mothers at the Sungai Paduan Community Health Center (UPTD). A quasi-experimental study with a post-test-only control group design was conducted involving 40 postpartum mothers selected through purposive sampling. Participants were assigned to either an intervention group receiving oxytocin massage or a control group receiving routine postpartum care. Breast milk production was assessed using breastfeeding frequency, breastfeeding duration, expressed milk volume, and infant urination and defecation frequency. Data were analyzed using the Mann-Whitney test. The findings revealed that 85% of mothers in the intervention group experienced smooth breast milk production compared with only 30% in the control group. Statistical analysis demonstrated a significant difference between groups (p < 0.001), with a large effect size (r = 0.61), indicating the substantial effectiveness of oxytocin massage. In conclusion, oxytocin massage is an effective non-pharmacological intervention for improving breast milk production and should be considered as part of routine postpartum care to support successful exclusive breastfeeding.